Employee perceptions of a workplace HIV testing intervention. Issue 5 (1st October 2018) - Blake, Holly; Hussain, Basharat; Hand, Jenny; Rowlands, David; Juma, Amdani; Evans, Catrin
Abstract : Purpose: There is a need to increase access to HIV testing in the UK in male migrant communities. The purpose of this paper is to assess the uptake and acceptability of a workplace HIV testing intervention aimed at increasing access to testing in non-clinical settings. Design/methodology/approach: A total of 20 health check events were delivered at 11 UK organisations employing male migrant workers. Intervention included HIV testing, cholesterol, BMI, blood glucose, blood pressure; tailored health advice; take-away resources; optional post-event text reminders about HIV and general health. Mixed-methods evaluation included exit questionnaires ( n =771), follow-up text messages ( n =465) and qualitative interviews ( n =35) to assess event acceptability. Qualitative data were analysed thematically. Findings: Attendees were 776 employees from 50 countries (51 per cent male; 30 per cent migrant workers). A total of 52 per cent of attendees undertook an HIV test (75 per cent were first-time testers). In total, 96 per cent considered HIV testing to be an acceptable element of workplace health checks; 79 per cent reported new health-related knowledge; 60 per cent of attendees opted for follow-up text messaging; 26 per cent of text respondents reported independently taking HIV test post-event. High acceptability and uptake of HIV testing was associated with convenience, opportunity taking (through removal of deliberation and intentional test-seeking), and normalisation of HIV testing within a general health check. Originality/value: This study is the first to demonstrate that opt-in HIV testing can be successfully delivered in the workplace within a multi-component health check. The workplace is an effective means of increasing access to HIV testing in groups at risk for HIV, including male migrant workers.